Metode Belajar SQ3R (Survey, Question, Read, Recite, Review) Dalam Upaya Peningkatan Pemahaman Bacaan Siswa - Sobri Sobri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
The aim of the research is to know the effectiveness of SQ3R method (Survey, Question, Read, Recite, Review) in improving student reading comprehension in indonesia language. The method of the research is qualitative approarch by using obsevation technique and literary study based on the relevant resources in improving student reading comprehension. The result of the research is SQ3R method can improve student reading comprehension. It can be seen that student be active and focus readers so that they can comprehend the texts both implicit and explici effectively, there is improving ability to communicative, and the diffrences of average student reading score in indonesia language at the tenth grade of sma Mathla’ul Anwar Menes-Pandeglang-Banten. In short SQ3R method is effective to use in improving students reading comprehension. How ever, there is weaknesses in this research, it is better to do further research using more observation to get accurate data.